Pengembangan Media Pembelajaran Interaktif Berbasis Camtasia Studio 8.0 pada Materi Sudut di Kelas IV MI Iskandar Sulaiman Batu - Aniyati, Kholis; Mustova, Mustova (FONDATIA, 2025)
Mathematics instruction at the primary school level remains predominantly focused on procedural skills and one-way communication, resulting in students’ limited conceptual understanding, particularly in determining angle measures. This study aims to (1) identify instructional needs in teaching angles using Camtasia Studio 8.0 and (2) evaluate the effectiveness and appeal of this digital medium in enhancing learning outcomes. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation phases. The participants consisted of 53 fourth-grade students divided into a control class (IV A) and an experimental class (IV B). Data were collected through expert validation, questionnaires, interviews, and learning outcome tests (pretest–posttest), and analyzed using both quantitative and qualitative methods. Validation results indicated that Camtasia Studio 8.0 achieved feasibility ratings of 80% (content expert), 96.5% (media expert), and 92.7% (instructional expert), confirming its validity and appropriateness for classroom use. The t-test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference in learning outcomes between the experimental and control groups. These findings support Mayer’s Multimedia Learning Theory, which posits that the integration of visuals, audio, and text enhances understanding and long-term memory retention. This study offers theoretical contributions to the integration of digital multimedia in mathematics education and presents an innovative, practical media model for primary school teachers.